Implementation of the Waste Bank Program in Strengthening Religious Character and Environmental Concern of the Community in Kraton Hamlet, Pekalongan City - Naila Rizqiyana; Riza Amelia; Nur Azka Dhiayul Aulia; Muhlisin Muhlisin; Abul Mafaakhir (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Many urban areas, including Pekalongan City, face significant waste management challenges. The accumulation of household waste is driven by population growth, increased consumption patterns, and a lack of awareness of how to independently sort and process waste, leading to increased environmental pollution. This study, entitled "Implementation of the Waste Bank Program to Strengthen Religious Character and Environmental Awareness in the Kraton Hamlet of Pekalongan City," aims to examine how the implementation of the Waste Bank Program helps increase religious and environmental awareness in the Kraton Hamlet of Pekalongan City. This study uses a qualitative approach with a case study design through observation, interviews, and documentation techniques. The results show that the Waste Bank can combine religious values with hygiene practices, increasing community discipline and spiritual awareness. In addition, this program encourages residents to actively participate in sorting and managing waste, increasing environmental awareness. Therefore, the Waste Bank Program is a good way to increase community faith and environmental awareness.